ANALISIS FAKTOR YANG MEMPENGARUHI KUNJUNGAN WISATAWAN MANCA NEGARA KE INDONESIA - Wawan Hermawan (Universitas Negeri Medan, 2016)
The tourism sector is a sector that can be relied on to earn foreign exchange.Revenue from tourism showed significant progress and continues to grow, so bringa high impact on the Indonesian economy. Number of tourists visiting foreigncountries is an important indicator for the growth of tourism sector in Indonesia isrelated to the increase in foreign exchange. Increase or decrease of tourist arrivals isinfluenced both by internal factors such as the condition of tourist destinations inIndonesia, politics and security in Indonesia or external factors such as the economic conditions of the various countries of origin of foreign tourists. This study uses panel data with the annual number of tourist arrivals from a number of countries to Indonesia for 19 years as the dependent variable. The independent variable of this research is RGDPP (Real GDP Per Capita), RREER (Relative Real Effective Exchange Rate), TCPI (Indicative Ratio of Consumer Price Index), Population, CPITUNIS (Consumer Price Index Tunisia), TO (Trade Openness). The results of this study indicate that tourist arrivals to Indonesia is heavily influenced by the distance from their home country to destinations in Indonesia. This variable is the biggest variable affecting the arrival of foreign tourists to Indonesia. Income per capita is the second largest variable and has a coefficient close to unity, so that the income elasticity of country of origin is an important variable to be considered.